2016
DOI: 10.1016/j.msard.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Binocular low-contrast letter acuity and the symbol digit modalities test improve the ability of the Multiple Sclerosis Functional Composite to predict disease in pediatric multiple sclerosis

Abstract: Background Outcome measures to capture disability, such as the Multiple Sclerosis Functional Composite (MSFC), were developed to enhance outcome measurements for clinical trials in adults with multiple sclerosis (MS). The MSFC initially included three components: a timed 25-foot walk [T25FW], 9-hole peg test [9HPT], and the Paced Auditory Serial Addition Task [PASAT]. Modifications to the original MSFC, such as adding binocular low-contrast letter acuity (LCLA) or substituting the symbol digit modalities test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…These contrasting findings may be secondary to our study population, which includes a larger age- and sex-matched control population. Consistent with a prior report, 16 our data support the utility of the 9HPT to reliably discriminate pediatric MS patients from healthy controls. With a median disease duration of 2 years in this cohort, our collective data would suggest that early impairments in several neurocognitive and physical domains are present and quantifiable via the metrics studied.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These contrasting findings may be secondary to our study population, which includes a larger age- and sex-matched control population. Consistent with a prior report, 16 our data support the utility of the 9HPT to reliably discriminate pediatric MS patients from healthy controls. With a median disease duration of 2 years in this cohort, our collective data would suggest that early impairments in several neurocognitive and physical domains are present and quantifiable via the metrics studied.…”
Section: Discussionsupporting
confidence: 92%
“…SDMT has been considered a valid tool to assess this particular impairment in patients with MS and has been an outcome measure of interest, particularly for pediatric MS clinical trials. 1214,16 Like these previous publications, our data support the use of the SDMT in discriminating between healthy, non-MS peers and pediatric MS patients. Interestingly, performance variability among the MS cohort was relatively low, despite variable disease durations.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These studies reported that patients with pediatric MS experience significantly worse fatigue than healthy controls. Overall, the results of the European studies were similar to those from the North American studies, highlighting fatigue as a common symptom experienced by patients with pediatric MS. (32,59,(73)(74)(75)(76)(77)(78)(79)(80). In these studies, the percentage of patients with cognitive impairment ranged from 32% to 35%.…”
Section: Fatiguementioning
confidence: 99%